2017
DOI: 10.18632/oncotarget.19816
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year observation of testosterone deficiency in Chinese patients with chronic heart failure

Abstract: Testosterone deficiency is present in a certain proportion men with chronic heart failure (CHF). Low testosterone levels in American and European patients with CHF lead to the high mortality and readmission rates. Interestingly, this relationship has not been studied in Chinese patients. To this end, 167 Chinese men with CHF underwent clinical and laboratory evaluations associated with determinations of testosterone levels. Total testosterone (TT) levels and sex hormone-binding globulin were measured by chemil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…The prognostic value of testosterone was demonstrated in 167 Chinese men with CHF who were followed up for at least 3 years. 60 Compared with those with normal testosterone levels, patients with low testosterone levels had more severe cardiac dysfunction, a higher prevalence of ischemic etiology, and more comorbidities. Readmission rates were also higher for patients with low testosterone levels than for patients in the normal testosterone group.…”
Section: Testosterone In Heart Failure Patientsmentioning
confidence: 99%
“…The prognostic value of testosterone was demonstrated in 167 Chinese men with CHF who were followed up for at least 3 years. 60 Compared with those with normal testosterone levels, patients with low testosterone levels had more severe cardiac dysfunction, a higher prevalence of ischemic etiology, and more comorbidities. Readmission rates were also higher for patients with low testosterone levels than for patients in the normal testosterone group.…”
Section: Testosterone In Heart Failure Patientsmentioning
confidence: 99%
“…Moreover, T2D patients with low T levels had poor glycemic control and increased insulin resistance, which may contribute to the longer duration of diabetes [7]. Very recently, researchers confirmed that type 2 diabetic men, especially those with low TT concentrations, have increased all-cause mortality [8,9], leading to a high prevalence of worsening cardiac function, ischemia, and readmission rate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of HF aetiology, anaemia has been associated with worsening HF 39 just like low ALM. 40 In univariable and multivariable logistic regression analysis for each group separately, only ALM in patients with dilated cardiomyopathy was independently associated with absolute peak VO 2 (median value), implying that the association seen in our results was driven by a higher ALM of these patients (Table 3).…”
Section: Discussionmentioning
confidence: 55%
“…A deficiência anabólica hormonal em pacientes com ICFEr também apresenta associação com um aumento significativo de peptídeo natriurético cerebral (BNP), importante marcador de pior prognóstico nesta população 34,36 . Ademais, pacientes com ICFEr e deficiência anabólica hormonal, quando comparados com seus pares sem deficiência, apresentam maior tempo de internação e uma maior frequência de readmissão 40,41 . Diversos estudos também têm demonstrado o impacto da deficiência anabólica hormonal sobre a mortalidade de pacientes com ICFEr, independente do eixo anabólico acometido 40,41 .…”
unclassified
See 1 more Smart Citation